Integrated Soil Fertility Management Enhances Soil Properties, Yield, and Nitrogen Use Efficiency of Rice Cultivation: Influence of Fertilizer Rate, Humic Acid, and Gypsum - Hartina; Tidarat Monkham; Patma Vityakon; Tanabhat-Sakorn Sukitprapanon (Agronomy, 2025)
Integrated soil fertility management is essential for improving soil productivity, rice yield, and nitrogen use efficiency (NUE). This study investigated the combined effects of the chemical fertilizer rate, humic acid (HA), and flue gas desulfurization gypsum (FG) on the soil chemical properties, rice yield, NUE, and nitrogen agronomic efficiency (NAE) in acidic paddy soil. The following three factors were evaluated: (1) fertilization based on farmer practices and rice nutrient requirements; (2) HA at 0 and 975 kg ha−1; and (3) FG at 0, 23, and 636 kg ha−1. Fertilization based on rice requirements reduced the nitrogen (N) input by 14.5% compared to farmer practices while still maintaining similar grain yields. Under farmer practice, HA enhanced total N content, cation exchange capacity (CEC), rice yield, NUE, and NAE. HA with FG (636 kg ha−1) increased total organic carbon (TOC) levels, total N levels, and exchangeable ammonium nitrogen (NH4-N), but decreased the yield. In contrast, HA combined with FG at 23 kg ha−1 enhanced the soil exchangeable Ca and S levels, as well as resulting in a high rice yield (7.7 t ha−1), NUE (39%), and NAE (32 kg kg−1). The findings suggest that to maintain farmer fertilization practices while improving soil properties and rice yield, HA should be applied with FG (23 kg ha−1).